Proximální karpektomie – pětileté výsledky - Švarc, A; Pilný, J; Repko, M; Kastenberger, T; Eichinger, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY This study aims to evaluate the results of patients treated by proximal row carpectomy at a follow-up of at least 5 years after the surgery. MATERIAL AND METHODS A total of 25 patients were treated by proximal row carpectomy for degenerative changes of the wrist as a consequence of the previous trauma or avascular necrosis of the lunate bone, of whom 21 patients underwent a follow-up examination at least 5 years postoperatively. Proximal row carpectomy was indicated in 15 patients for SLAC wrist, in 4 patients for avascular necrosis of the lunate bone, in 1 patient for SNAC wrist, and in 1 patient for inveterate dislocation of the wrist. The follow-up clinical and radiological examinations were performed at least 5 years after the surgery. The range of wrist motion, grip strength, presence of pain at rest or pain under loads, total clinical score according to the Green and O'Brien scoring system, patient satisfaction with the outcome of surgery were assessed. By fluoroscopy the range of wrist motion, degenerative changes of the radiocapitate joint, and translation of the capitate bone with respect to the distal radius were evaluated. RESULTS Postoperative improvements in the range of motion and grip strength were confirmed. Also, the pain relief at rest and under loads was achieved. Five years after the surgery, most of the patients (85.6%) reported an overall improvement. The total clinical score according to the Green and O'Brien scoring system improved from 35.8 preoperatively to 63.1 postoperatively. DISCUSSION The advantage of this procedure is a low percentage of complications, relative technical simplicity, maintenance of functional motion of the wrist, satisfactory grip strength, and pain relief. There are no complications related to the implant, no risk of a non-union. CONCLUSIONS As shown by our results obtained 5 years after the surgery as well as the published data, in the indicated cases the proximal row carpectomy is an appropriate surgical technique to treat the degenerative changes of the wrist. In most of the patients, favourable functional results and pain relief can be expected. Key words:proximal row carpectomy, SLAC wrist, SNAC wrist, avascular necrosis of the lunate bone, dislocation of the wrist.
Keywords: síla ruky; Hand Strength; radiografie; Radiography; Arthralgia; výsledek terapie; Lunate Bone; ortopedické výkony; lidé; nekróza; artralgie; pooperační komplikace; Treatment Outcome; následné studie; Necrosis; Range of Motion, Articular; Joint Dislocations; kosti zápěstní; rozsah kloubních pohybů; Follow-Up Studies; Orthopedic Procedures; Postoperative Complications; Carpal Bones; dislokace kloubu; poloměsíčitá kost; Humans